Millesgården - Qvist, Per (2006)
Millesgården is a museum on the island of Lidingö outside Stockholm. It contains the buildings which were the home and studios of the artist Carl Milles and his artist wife Olga. It also contains the grounds that originated as the garden of their home. Carl Milles later developed the garden into a sculpture park where a great part of the sculptors works are on display. In this report only the sculpture park is treated. The park is now approaching an age of 100 years. During the first half century of its existence, the artist Carl himself was the main propelling factor behind the design and development of the park. After his death, the work in the park has been concentrated on preservation and maintenance. The basic features of the park are still the same as when the artist died. Its character though, has changed over the years due to wear and tear, the dynamics of the plant material and insufficient resources for maintenance. Some minor additions have also been made. One of the main purposes of the master thesis has been to ameliorate the accessibility of the park that is bad due to the topography and the status of sealed surfaces.